Greco-Egyptian interactions: literature, translation, and culture, 500 BC-AD 300 - Rutherford, Ian (Oxford University Press, 2016)
This volume examines the cultural interaction between Greek and Egyptian culture, which can be traced in different forms over more than a millennium. Focusing in particular on literature and textual culture, chapters from leading experts cover a wide range of topics such as religion, philosophy, historiography, romance, and translation.
Keywords: Egypt -- Relations -- Greece; Greece -- Relations -- Egypt; Egypt -- Civilization -- Greek influences; Greece -- Civilization -- Egyptian influences; Greece -- Intellectual life; Egypt -- Intellectual life; Konferenzschrift -- 17.09.2007-19.09.2007 -- Reading; Geschichte 500 v. Chr.-300 v. Chr.; Ägypten; Kulturkontakt; Griechenland